A method for predicting and evaluating the uniformity of efflorescence in microbially resistant glass fiber reinforced cement products.
Through the prediction and evaluation method based on microbial anti-panol, combined with accelerated panol-alol treatment and image method, the problem of difficult anti-panol-alol properties of glass fiber reinforced cement products is solved, and high-precision and short-cycle quantitative evaluation is achieved.
Patent Information
- Application Number
- CN202110479138.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-04-29
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-04-29
AI Technical Summary
The prior art is difficult to effectively predict and evaluate the anti-panol properties of glass fiber reinforced cement products, and the panolol test cycle is long and unstable, which increases the difficulty of characterizing anti-panol performance.
The prediction and evaluation method based on microbial anti-panol is used, and the anti-panol properties of glass fiber reinforced cement products are calculated by accelerating panol alkali treatment and image method combined with Raul color card method to calculate the panol alkali area ratio and panol alkali uniformity on the surface of the test piece, and the anti-panol properties of glass fiber reinforced cement products are quantitatively evaluated.
Accurate prediction and quantitative evaluation of the uniformity of the alkaline in glass fiber reinforced cement products is achieved, with a short evaluation period and high accuracy, filling the technical gap in this field.
Smart Images

Figure CN113192032B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of building materials, and in particular to a method for predicting and evaluating the anti-efflorescence performance of cement products. Background Art
[0002] Glass fiber reinforced cement products are one of the most influential and widely used products in China's decorative cement-based materials. They are also applicable to modern architecture and interior decoration because of their light weight, simple installation, high strength, and the ability to be prefabricated in factories in large quantities, which shortens the construction period. The biggest difference between glass fiber reinforced cement and other decorative cement-based materials is that alkali-resistant glass fiber is added as a reinforcing material in its structural layer, giving it better mechanical properties, and its decorative aesthetic properties are mainly provided by the surface layer.
[0003] The efflorescence problem is a key issue restricting the use of decorative cement-based materials including glass fiber reinforced cement products. The efflorescence phenomenon is caused by the migration of moisture inside the cement-based material and the soluble salts brought out by the evaporation of surface moisture, which forms white deposits on the surface of the cement-based material, seriously affecting the decorative effect of the finishing mortar. Summary of the invention
[0004] Purpose of the invention: The purpose of the present invention is to provide a method for predicting and evaluating the efflorescence uniformity of glass fiber reinforced cement products based on microbial anti-efflorescence, which can accurately predict the efflorescence uniformity of such cement products, and at the same time can realize the quantitative evaluation of glass fiber reinforced cement products added with microbial anti-efflorescence agents, with a short evaluation cycle and high accuracy.
[0005] Technical solution: The method for predicting and evaluating the efflorescence uniformity of glass fiber reinforced cement products based on microbial anti-efflorescence described in the present invention is to subject the test piece to an accelerated efflorescence treatment, and then use the image method and the RAL color card to refer to the color of the efflorescence substance. After the accelerated efflorescence treatment, the efflorescence area rate and efflorescence uniformity of the test piece surface are obtained, thereby obtaining a quantitative evaluation index for the anti-efflorescence performance of glass fiber reinforced cement products.
[0006] The specific steps include:
[0007] (1) Accelerating efflorescence treatment of glass fiber reinforced cement products mixed with microbial anti-efflorescence agent;
[0008] (2) collecting images of the specimen after accelerated efflorescence treatment to obtain a specimen surface image, binarizing the specimen surface image to obtain a black-and-white image, and calculating the efflorescence area rate of the specimen;
[0009] (3) The black-and-white image is divided according to different visual directions, and the efflorescence area rate of each area is calculated and obtained to obtain the efflorescence uniformity of the specimen.
[0010] Furthermore, according to the efflorescence area ratio and efflorescence uniformity of the surface layer and the base layer, the trend of the anti-efflorescence performance of the GRC specimens with different dosages of microbial anti-efflorescence agent was predicted.
[0011] Preferably, the efflorescence area ratio and efflorescence uniformity of the glass fiber reinforced cement product are as follows:
[0012] E u =0.1217+0.02762×0.2752 f :
[0013] When adding microbial anti-efflorescence agent, the efflorescence area rate and efflorescence uniformity are as follows:
[0014] E u =0.03567+0.1309×0.3814 m :
[0015] In the formula, E a is the efflorescence area rate, E u is the uniformity of efflorescence, f and m are the percentage of fiber and microorganism in the mass of cementitious materials, respectively.
[0016] In the above step (1), the preparation method of the microbial anti-efflorescence glass fiber reinforced cement product comprises: firstly pouring a surface layer of the glass fiber reinforced cement product on a formwork, and adding a microbial anti-efflorescence agent to the surface layer; then before the surface layer begins to set, pouring a base layer on the surface layer, and adding alkali-resistant glass fiber to the base layer.
[0017] In step (1), the accelerated efflorescence treatment is to place the glass fiber reinforced cement specimen after molding and demolding in a water tank, add water to more than half of the specimen height and ensure that the upper surface of the specimen to be tested is in a wet state, apply a constant wind speed to the surface, and place it for 24 to 48 hours. During this period, water is added to the water tank to ensure that the water surface is located at more than half of the specimen height. The main active ingredient of the microbial anti-efflorescence agent is microbial powder, and the constant wind speed applied is 2m / s, in order to shorten the test period and better test the anti-efflorescence performance of glass fiber reinforced cement products.
[0018] The length of the surface layer and the base layer is 200-400 mm, the width is 200-400 mm, and the height is 10-20 mm.
[0019] Preferably, in order to ensure that the Ca 2 + It is fixed before migrating to the surface of cement-based materials, and CaCO3 is generated inside the cement-based materials rather than on the surface; the time interval between pouring the surface layer and the base layer shall not exceed 10 minutes, and the formed specimens shall be placed in a standard curing room with a temperature of 20±2℃, and the relative humidity of the curing room shall be greater than 95%.
[0020] Step (2) comprises the following steps:
[0021] (1) Under constant light source conditions, the RAL9010 color card and the surface image of the GRC specimen after accelerated efflorescence treatment were collected on the same screen, and the images were converted into black and white images with only grayscale changes;
[0022] (2) Read the grayscale value of the RAL9010 color card and record it as G. Count the area A of the area whose grayscale value is less than G in the binary image of the GRC product surface E And the total area A0 of the binary image of the surface of the GRC product to be tested;
[0023] (3) Calculation of efflorescence area ratio E a
[0024]
[0025] In the formula, E a A is the efflorescence area ratio, E is the area of the region whose gray value is less than G in the binary image of the surface to be measured, and A0 is the total area of the binary image of the surface to be measured.
[0026] Among them, the detection of efflorescence area rate adopts the image method, uses a 40-million-pixel camera for image acquisition, and uses the RAL color card as a reference for the color of the efflorescence substance, in order to intuitively derive the anti-efflorescence performance of glass fiber reinforced cement products.
[0027] Step (3) includes dividing the collected GRC surface image into different regions and calculating the efflorescence area rate E of each region respectively. ai , efflorescence uniformity E u Use the following formula to calculate:
[0028]
[0029]
[0030] In the formula, E u E is the uniformity of efflorescence, ai is the efflorescence area ratio of the i-th region, It is the average value of the efflorescence area rate in each region.
[0031] In step (3), five visual directions are used to divide the image, and the image division lines are respectively along the vertical direction, the horizontal direction, the 45° direction, the 135° direction and the center divergence direction.
[0032] Principle of the invention: The present invention prepares microbial anti-efflorescence glass fiber reinforced cement products with a surface layer and a base layer respectively, wherein a microbial anti-efflorescence agent is added to the surface layer, and alkali-resistant glass fiber is added to the base layer. Before conducting the anti-efflorescence performance test, the test piece is first subjected to an accelerated efflorescence treatment to shorten the test period, and then the image method is used in conjunction with the RAL color card to refer to the color of the efflorescence substance, followed by the discrete degree of the efflorescence area rate of different unit areas on the surface of the glass fiber reinforced cement from five visual directions. After the accelerated efflorescence treatment, the efflorescence area rate of the test piece is obtained, and the test piece is divided from different viewing angles and the efflorescence area rate is calculated respectively, and the standard deviation is calculated to obtain the efflorescence uniformity.
[0033] The technical difficulty of the present invention is that the microbial anti-efflorescence agent and alkali-resistant glass fiber are introduced into the microbial anti-efflorescence cement product, and the internal microstructure and transmission mechanism are extremely complex compared with ordinary cement-based materials. Due to the influence of the two on the internal porosity, pore size distribution and other pore structures of the product, the anti-efflorescence performance of the microbial anti-efflorescence glass fiber reinforced cement product is difficult to quantitatively evaluate and predict, and the efflorescence test cycle is long and unstable, which increases the difficulty of characterizing and testing its anti-efflorescence performance.
[0034] Beneficial effects:
[0035] By combining theoretical simulation and experimental verification, the present invention proposes a new anti-efflorescence performance test method, quantitative evaluation index and prediction model, which fills the technical gap in this field and realizes the quantitative evaluation and accurate prediction of microbial anti-efflorescence glass fiber reinforced cement products.
[0036] The efflorescence uniformity of glass fiber reinforced cement products adopts the discrete degree of efflorescence area rate of different unit areas on the surface of glass fiber reinforced cement in different visual directions, comprehensively analyzes the efflorescence uniformity test image, and greatly improves the accuracy. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a principle flow chart of the present invention.
[0038] Figure 2 The present invention collects the test piece and the color card image on the same screen.
[0039] Figure 3 This is a visual direction division diagram of the efflorescence uniformity test image of the present invention, (a) is the vertical direction, (b) is the horizontal direction, (c) is the 45° direction, (d) is the 135° direction, and (e) is the central divergence direction;
[0040] Figure 4Figure 1 is a test diagram of the efflorescence area rate of the mortar surface layer (M group) of the glass fiber reinforced cement product of the present invention, (a) is a grayscale image of M0, (b) is a image after M0 binarization, (c) is a grayscale image of M2, (d) is a image after M2 binarization, (e) is a grayscale image of M4, (f) is a image after M4 binarization, (g) is a grayscale image of M6, and (h) is a image after M6 binarization;
[0041] Figure 5 This is a graph showing the anti-efflorescence performance of the glass fiber reinforced cement product mortar surface layer (Group M) of the present invention;
[0042] Figure 6 Figure 1 is a test diagram of the efflorescence area rate of the mortar surface layer (J group) of the glass fiber reinforced cement product of the present invention, (a) is a grayscale image of J0, (b) is a image after J0 is binarized, (c) is a grayscale image of J1, (d) is a image after J1 is binarized, (e) is a grayscale image of J3, (f) is a image after J3 is binarized, (g) is a grayscale image of J5, and (h) is a image after J5 is binarized;
[0043] Figure 7 This is a graph showing the anti-efflorescence performance of the glass fiber reinforced cement product mortar surface layer (Group J) of the present invention;
[0044] Figure 8 : are the images after M0J0 and M2J0 are binarized according to the present invention, (a) is the grayscale image of M0J0, (b) is the image after M0J0 is binarized, (c) is the grayscale image of M2J0, and (d) is the image after M2J0 is binarized;
[0045] Fig. 9 : are the images after M4J0 and M6J0 binarization processing of the present invention, (a) is the grayscale image of M4J0, (b) is the image after M4J0 binarization processing, (c) is the grayscale image of M6J0, and (d) is the image after M6J0 binarization processing;
[0046] Fig.10 : are the images after binarization processing of M0J1 and M2J1 of the present invention, (a) is the grayscale image of M0J1, (b) is the image after binarization processing of M0J1, (c) is the grayscale image of M2J1, and (d) is the image after binarization processing of M2J1;
[0047] Fig.11 : are the images after binarization processing of M4J1 and M6J1 of the present invention, (a) is the grayscale image of M4J1, (b) is the image after binarization processing of M4J1, (c) is the grayscale image of M6J1, and (d) is the image after binarization processing of M6J1;
[0048] Fig.12Figures 1 and 2 are the images of M0J3 and M2J3 after binarization processing of the present invention, (a) is the grayscale image of M0J3, (b) is the image of M0J3 after binarization processing, (c) is the grayscale image of M2J3, and (d) is the image of M2J3 after binarization processing;
[0049] Fig.13 The figures are the images after binarization of M4J3 and M6J3 of the present invention, (a) is the grayscale image of M4J3, (b) is the image after binarization of M4J3, (c) is the grayscale image of M6J3, and (d) is the image after binarization of M6J3;
[0050] Fig.14 Figures 2 and 3 are the images of M0J5 and M2J5 after binarization processing of the present invention, (a) is the grayscale image of M0J5, (b) is the image of M0J5 after binarization processing, (c) is the grayscale image of M2J5, and (d) is the image of M2J5 after binarization processing;
[0051] Fig.15 Figures 1 and 2 are the images of M4J5 and M6J5 after binarization processing of the present invention, (a) is the grayscale image of M4J5, (b) is the image of M4J5 after binarization processing, (c) is the grayscale image of M6J5, and (d) is the image of M6J5 after binarization processing;
[0052] Fig.16 is the overall efflorescence area ratio of the glass fiber reinforced cement product of the present invention;
[0053] Fig.17 The following are examples of the division of the area for calculating the uniformity of efflorescence in the present invention, where (a) and (b) are the first and second parts divided in the vertical direction, (c) and (d) are the third and fourth parts divided in the horizontal direction, (e) and (f) are the fifth and sixth parts divided in the 45° direction, (g) and (h) are the seventh and eighth parts divided in the 135° direction, and (i) is the tenth part divided in the central divergent direction;
[0054] Fig.18 This is a diagram showing the calculation results of the efflorescence uniformity of the present invention. DETAILED DESCRIPTION
[0055] The present invention is further described in detail below in conjunction with the embodiments.
[0056] like Figure 1 The figure shows a flow chart of the inventive principle of the present invention. First, the specimen is subjected to an accelerated efflorescence treatment, and then the image method is used in conjunction with the RAL color card to refer to the color of the efflorescence substance. After the accelerated efflorescence treatment, the efflorescence area rate and efflorescence uniformity of the specimen surface are obtained, thereby obtaining a quantitative evaluation index for the efflorescence resistance of glass fiber reinforced cement products; according to the efflorescence area rate and efflorescence uniformity of the surface layer and the base layer, the trend of the efflorescence resistance of the GRC specimens with different dosages of microbial anti-efflorescence agents is predicted.
[0057] Among them, the efflorescence area rate and efflorescence uniformity of glass fiber reinforced cement products are as follows:
[0058] E u =0.1217+0.02762×0.2752 f :
[0059] When adding microbial anti-efflorescence agent, the efflorescence area rate and efflorescence uniformity are as follows:
[0060] E u =0.03567+0.1309×0.3814 m :
[0061] In the formula, E a is the efflorescence area rate, E u is the uniformity of efflorescence, f and m are the percentage of fiber and microorganism in the mass of cementitious materials, respectively.
[0062] The specific steps are as follows:
[0063] (1) First, a glass fiber reinforced cement surface layer is formed in a mold with a smooth surface, that is, PW42.5 grade white cement, medium sand, colorant, and microbial anti-eluviation agent are mixed, water and water reducer are mixed with powder, and poured on the mold; then, before the initial setting of the surface layer, a glass fiber reinforced cement base layer is formed on the basis of the surface layer, that is, PW42.5 grade white cement, medium sand, and colorant are mixed, water and water reducer are mixed with powder, and alkali-resistant glass fiber is added during the mixing process, and poured on the surface layer;
[0064] The main component of the microbial anti-pan-alkali agent added in this embodiment is Bacillus subtilis, and the fiber is short-cut alkali-resistant glass fiber with a length of about 2 cm and a diameter of about 0.2-0.3 mm.
[0065] (2) Place the demolded specimen in a water tank, add water to more than half the height of the specimen and ensure that the upper surface of the specimen to be tested is wetted. Apply a constant wind speed to the surface and place it for 24 hours before taking it out for anti-efflorescence performance test;
[0066] (3) Under constant light source conditions, the surface images of the RAL9010 color card (pure white) and the GRC specimen after accelerated alkali treatment were collected on the same screen, and the images were imported into the computer. The images were converted into black and white images with only grayscale changes using Image-J software. The grayscale value of the RAL9010 color card was read as G, and then the area A of the GRC product surface with a grayscale value less than G was counted. E And the total surface area A0 of the GRC product to be tested, the efflorescence area rate is calculated as follows:
[0067]
[0068] Where: E a ——efflorescence area rate; A E ——The area of the region whose gray value is less than G in the binary image of the surface to be measured; A0——The total area of the binary image of the surface to be measured;
[0069] (4) The collected GRC surface map is divided into different areas, and the efflorescence area rate Eai of each area is calculated respectively. The efflorescence uniformity is calculated using the following formula:
[0070]
[0071]
[0072] Where: E u ——Evenness of efflorescence; E ai ——the efflorescence area ratio of region i; ——The average value of efflorescence area rate in each region;
[0073] (5) Design of glass fiber reinforced cement product surface mix ratios including M0, M2, M4 and M6, and design of glass fiber reinforced cement product base mix ratios including J0, J1, J3 and J5;
[0074] Table 1. Mixing ratio of glass fiber reinforced cement products surface layer
[0075]
[0076]
[0077] Table 2. Mixing ratio of glass fiber reinforced cement products
[0078] J0 J1 J3 J5 Cement Type White White White White Cement / kg 2.4 2.4 2.4 2.4 Mortar-sand ratio 1:1 1:1 1:1 1:1 Water-cement ratio 0.35 0.35 0.35 0.35 fiber / % 0 1 3 5 Anti-efflorescence agent / % 0 0 0 0 <![CDATA[Fe2O3 pigment / %]]> 5 5 5 5 Water reducing agent / % 0.3 0.3 0.3 0.3
[0079] (6) A group of glass fiber reinforced cement products are respectively selected from the surface layer and the base layer to be molded. When the test pieces are assembled during molding, the glass fiber reinforced cement surface layer is first molded in a mold with a smooth surface, and then the glass fiber reinforced cement base layer is molded on the basis of the surface layer;
[0080] (7) forming glass fiber reinforced cement surface layer specimens with different anti-efflorescence agent dosages according to the proportions shown in step (6), and obtaining the efflorescence area rate and efflorescence uniformity of the specimens after accelerated efflorescence treatment;
[0081] (8) The specimen is divided from five different perspectives and the efflorescence area rate is calculated respectively. The standard deviation is calculated to obtain the efflorescence uniformity, and the final analysis is performed to obtain the results.
[0082] like Figure 3-5 As shown, the main active ingredient of the microbial anti-efflorescence agent is microbial powder, and the constant wind speed applied is 2m / s. In order to shorten the test period and better test the anti-efflorescence performance of glass fiber reinforced cement products, the efflorescence area rate is detected by image method, and a 40-million-pixel camera is used for image acquisition. The RAL color card is used as a reference for the color of the efflorescence substance. In order to intuitively obtain the anti-efflorescence performance of glass fiber reinforced cement products, the efflorescence area rate and efflorescence uniformity are used to characterize it, which is convenient for comparative analysis of data in the next step. The efflorescence uniformity of glass fiber reinforced cement products is the discrete degree of the efflorescence area rate of different unit areas on the surface of glass fiber reinforced cement in five visual directions. In order to comprehensively analyze the efflorescence uniformity test image, the conclusion is more accurate.
[0083] like Figure 4-5 As shown in the figure, the molding size of the surface layer of the glass fiber reinforced cement product is 300mm×300mm×10mm, and the molding size of the base layer of the glass fiber reinforced cement product is 300mm×300mm×20mm. The time interval between the two layers of pouring does not exceed 10min. The molded specimens are placed in a standard curing room with a temperature of 20±2℃, and the relative humidity of the curing room is greater than 95%. In order to ensure that the Ca 2+ It is fixed before migrating to the surface of cement-based materials, and CaCO3 is generated inside the cement-based materials rather than on the surface. When the thickness of glass fiber reinforced cement products is 10 cm, when the dosage of microbial anti-efflorescence agent is 0%, 0.2%, 0.4%, and 0.6%, the efflorescence area rate of the glass fiber reinforced cement surface layer is 37.29%, 22.35%, 21.00%, and 10.61%, respectively. The results show that a certain amount of microbial anti-efflorescence agent can effectively improve the anti-efflorescence performance of the glass fiber reinforced cement surface layer, and for the efflorescence uniformity, when the dosage of microbial anti-efflorescence agent of the surface layer is 0%, 0.2%, 0.4%, and 0.6%, its values are 0.089, 0.043, 0.094, and 0.170, respectively.
[0084] like Figure 6-16 As shown in Table 4, glass fiber reinforced cement product base specimens with different anti-efflorescence agent dosages were formed according to the mix ratio shown in Table 4. The images after accelerated efflorescence treatment and binarization treatment are shown in Figure 4. Figure 5 As shown in the figure, the calculation results of the efflorescence area rate and efflorescence uniformity are as follows Figure 6 As shown in Table 1, when there is only a 20mm thick glass fiber reinforced cement product base layer, the fiber content is 0%, 1%, 3%, and 5%, and the efflorescence area rate of the specimen is 58.44%, 70.37%, 71.16%, and 80.4%, respectively, and the efflorescence uniformity is 0.149, 0.129, 0.123, and 0.121, respectively. According to the mix ratio shown in Table 1 and Table 2, the glass fiber reinforced cement product composed of the base layer and the surface layer is formed, as shown in Table 1. Figure 8-15 The images shown are of some specimens after accelerated efflorescence treatment and binarization treatment. Fig.15 is the calculation result of the efflorescence area rate. From the test results, it can be seen that in the GRC products including the surface layer and the base layer, the effect of the microbial anti-efflorescence agent on improving the anti-efflorescence performance of the GRC products is still very obvious: when the dosage of the microbial anti-efflorescence agent in the surface layer is 0% and 0.2%, the efflorescence area rate of the GRC product specimens in each group is above 60% or even reaches 80%; when the dosage of the microbial anti-efflorescence agent in the surface layer reaches 0.4%, the efflorescence area rates of the M4J0 and M4J1 groups have dropped to below 10%, which are 4.42% and 6.08% respectively, and the efflorescence area rates of the M4J3 and M4J5 groups have also decreased from 70% to 80% to 18.00% and 23.17%; when the dosage of the microbial anti-efflorescence agent in the surface layer reaches 0.6%, the efflorescence area rate of the GRC product specimens in each group is reduced to about 3%. In addition, when the dosage of microbial anti-efflorescence agent in the surface layer is constant, the efflorescence area rate shows a trend of increasing with the increase of the fiber dosage in the base layer, which is consistent with the above-mentioned test results. However, since the base layer is covered by the surface layer in the complete GRC product, the influence of the base layer efflorescence on the overall efflorescence is limited, and this trend is not as significant as when only the base layer exists.
[0085] like Figure 16-18 As shown, the specimen is divided from different perspectives and the efflorescence area rate is calculated respectively. The standard deviation is calculated to obtain the efflorescence uniformity. The calculation results are shown in Fig.18 As shown, combined Fig.16 , 18 It can be found that when the efflorescence area rate is large, the efflorescence uniformity value will also be larger, but the overall deviation is very small. This deviation is related to the definition and calculation method of efflorescence uniformity, while other factors such as microbial anti-efflorescence agents, alkali-resistant glass fibers, etc. have no direct effect on efflorescence uniformity.
[0086] In summary, the test and characterization method for the anti-efflorescence performance of glass fiber reinforced cement products is to subject the test piece to accelerated efflorescence treatment before the anti-efflorescence performance test to shorten the test cycle, and then use the image method and the RAL color card to refer to the color of the efflorescence material. Then, the discrete degree of the efflorescence area rate of different unit areas on the surface of the glass fiber reinforced cement is measured from five visual directions. A group of glass fiber reinforced cement products with mix ratios are selected from the surface layer and the base layer respectively. After accelerated efflorescence treatment, the efflorescence area rate and efflorescence uniformity of the test piece are obtained, and the test piece is divided from different viewing angles and the efflorescence area rate is calculated respectively, and the standard deviation is calculated to obtain the efflorescence uniformity.
Claims
1. A method for predicting and evaluating the uniformity of efflorescence of glass fiber reinforced cement products based on microbial anti-efflorescence, characterized in that: The following steps are involved: (1) Accelerating efflorescence treatment of glass fiber reinforced cement products mixed with microbial anti-efflorescence agent; (2) Capturing images of the specimen after accelerated efflorescence treatment to obtain a specimen surface image, binarizing the specimen surface image to obtain a black-and-white image, and calculating the efflorescence area rate of the specimen, specifically comprising: under constant light source conditions, capturing images of a RAL color card with a color number of RAL9010 and a surface image of a GRC specimen after accelerated efflorescence treatment on the same screen, and converting the images into black-and-white images with only grayscale changes; Read the gray value of the RAL9010 color card and record it as G. Count the area A of the area whose gray value is less than G in the binary image of the GRC product surface E And the total area A0 of the binary image of the surface of the GRC product to be tested; calculate the efflorescence area rate E a In the formula, E a A is the efflorescence area ratio, E is the area of the region with gray value less than G in the binary image of the surface to be measured, and A0 is the total area of the binary image of the surface to be measured; (3) Divide the black and white image according to different visual directions, calculate the efflorescence area rate of each area, and obtain the efflorescence uniformity of the specimen, which specifically includes: dividing the collected GRC surface image into different areas, and calculating the efflorescence area rate E of each area respectively. ai , efflorescence uniformity E u Use the following formula to calculate: In the formula, E u E is the uniformity of efflorescence, ai is the efflorescence area ratio of the i-th region, It is the average value of the efflorescence area rate in each region.
2. The method for predicting and evaluating efflorescence uniformity according to claim 1, characterized in that: According to the efflorescence area rate and efflorescence uniformity of the surface layer and the base layer, the trend of the anti-efflorescence performance of GRC specimens with different dosages of microbial anti-efflorescence agent was predicted.
3. The method for predicting and evaluating efflorescence uniformity according to claim 2, characterized in that: The efflorescence area rate and efflorescence uniformity of glass fiber reinforced cement products are as follows: When adding microbial anti-efflorescence agent, the efflorescence area rate and efflorescence uniformity are as follows: In the formula, E a is the efflorescence area rate, E u is the uniformity of efflorescence, f and m are the percentage of fiber and microorganism in the mass of cementitious materials, respectively.
4. The method for predicting and evaluating efflorescence uniformity according to claim 1, characterized in that: In step (3), five visual directions are used to divide the image, and the image division lines are respectively along the vertical direction, the horizontal direction, the 45° direction, the 135° direction and the center divergence direction.
5. The method for predicting and evaluating efflorescence uniformity according to claim 1, characterized in that: In step (1), the accelerated efflorescence treatment is to place the glass fiber reinforced cement specimen after molding and demolding in a water tank, add water to more than half of the specimen height and ensure that the upper surface of the specimen to be tested is in a wet state, apply a constant wind speed to the surface, and leave it for 24 to 48 hours. During this period, water is added to the water tank to ensure that the water surface is above half of the specimen height.
6. The method for predicting and evaluating efflorescence uniformity according to claim 1, characterized in that: In step (1), the preparation method of the microbial anti-efflorescence glass fiber reinforced cement product comprises: firstly pouring a surface layer of the glass fiber reinforced cement product on a formwork, and adding a microbial anti-efflorescence agent to the surface layer; then before the surface layer begins to set, pouring a base layer on the surface layer, and adding alkali-resistant glass fiber to the base layer.
7. The method for predicting and evaluating efflorescence uniformity according to claim 6, characterized in that: The time interval between pouring the surface layer and the base layer shall not exceed 10 minutes. The formed specimens shall be placed in a standard curing room with a temperature of 20±2℃ and a relative humidity of greater than 95%.
8. The method for predicting and evaluating efflorescence uniformity according to claim 1, characterized in that: The length of the surface layer and the base layer is 200-400 mm, the width is 200-400 mm, and the height is 10-20 mm.